2020
DOI: 10.3389/fpubh.2020.00371
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Web-Based Tool for Risk Assessment and Exposure Control Planning of Silica-Producing Tasks in the Construction Sector

Abstract: We describe the development and implementation of a novel, on-line risk assessment tool for respirable crystalline silica (RCS) exposure for use in the construction sector. It was motivated by the introduction of new OHS regulation in British Columbia that allowed for the substitution of exposure measurement data with “objective air monitoring data” collected at “equivalent work operations.” This allowance encouraged the introduction of quantitative risk assessment in a notoriously challenging work environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These include handling hazardous materials such as adhesives, solvents, and cleaning agents, as well as exposure to fumes, gases, dust, and fibers from building materials such as asbestos, etc. For instance, a construction worker may be involved in mixing and applying chemicals to treat concrete surfaces, or in sanding and cutting materials that generate fumes and dust [ 36 ]. Data have shown that workers in both the construction and manufacturing sectors were primarily exposed to chemicals or cosmetics, as well as fumes, gases, and dust.…”
Section: Discussionmentioning
confidence: 99%
“…These include handling hazardous materials such as adhesives, solvents, and cleaning agents, as well as exposure to fumes, gases, dust, and fibers from building materials such as asbestos, etc. For instance, a construction worker may be involved in mixing and applying chemicals to treat concrete surfaces, or in sanding and cutting materials that generate fumes and dust [ 36 ]. Data have shown that workers in both the construction and manufacturing sectors were primarily exposed to chemicals or cosmetics, as well as fumes, gases, and dust.…”
Section: Discussionmentioning
confidence: 99%
“…Some factors may be constant within a facility and gathered anytime during the exposure survey (such as general exhaust ventilation parameter), while others may vary in time requiring collection during air sampling (such as tasks, tools, amount of time in different locations) ( 41 ). Whereas, attempts to standardize the collection and storage of contextual information have not gained traction ( 15 , 18 , 21 , 22 , 25 , 26 , 41 , 42 ), numerous studies have successfully collected and used contextual information specific to their research to better understand the causes of variation or to predict exposures ( 41 43 ).…”
Section: Methods and Discussionmentioning
confidence: 99%
“…Personnel in the field have to deal with the instability of the drilling and production process. Activities such as overbalanced wells, gas leakages, and generally, the reactive nature of hydrocarbon resources tend to create life-threatening situations if not monitored well ( 22 ). That is why much of the literature has focused on the health safety environment (HSE) in the petrochemical, oil and gas sector.…”
Section: Literature Reviewmentioning
confidence: 99%